Saved by the Union: Romanians’ Attitudes toward the European Union - Ion Chiciudean; Nicoleta Corbu (Romanian Journal of Communications and Public Relations, 2015)
In this study we show that, in the aftermath of the economic crisis, Romanians remain among the most enthusiastic citizens of the European Union, in what concerns trust in the European institutions, projections for the future, the image of the EU and general attitudes toward the union. Relying on data provided by eurobarometers since the Romanian integration, we argue that the reasons for this peculiar position of Romanians within the EU is largely due to how people evaluate the economic and political performance of their own country: from evaluations of the economy to trust in national institutions, Romanians are very pessimistic about how their country handles the present situation and about perspectives for the future. In this context, they turn to the European Union as to a Savior, who represents their hope and promise for a better future, for economic prosperity and security. This is the reason why, more than five years after the beginning of the financial crisis, Romanians are still among the most optimistic citizens of Europe.